Comment from Guest Editors - Edward Brazee; Jeffrey Wilhelm (Journal of Research in Rural Education, 1997)
In spite of impressive gains for young adolescents in middle level schools in the last 40 years, the goals, purposes, and functions of middle schools remain remarkably undefined, for educators as well as for the lay-public. Two key documents, Turning Points: Preparing American Youth for the 21st Century by the Carnegie Corporation and This We Believe from the National Middle School Association, clearly outline the conceptual foundations and practical possibilities of today's middle schools. Concepts such as an adult advocate for each student, formation of teaching teams, integrated curriculum, and hands-on instruction are highlights of these documents and of middle schools themselves.